(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Mental health stigma continues to be a significant barrier to seeking and receiving adequate care for millions of individuals worldwide. In this article, we delve into the perspectives of medical doctors on the frontline of mental health care. Through interviews and surveys, we explore their insights, experiences, and strategies for addressing stigma within medical practice and society at large. By understanding the unique challenges faced by medical professionals in combating mental health stigma, we aim to shed light on effective interventions and foster a more supportive environment for those struggling with mental health conditions.